Dynamics of Fluorescent Dyes Attached to G‐Quadruplex DNA and their Effect on FRET Experiments. Issue 12 (14th July 2015) - Søndergaard , Siri; Aznauryan, Mikayel; Haustrup, Emil K.; Schiøtt , Birgit; Birkedal, Victoria; Corry, Ben
Abstract FRET spectroscopy is a promising approach for investigating the dynamics of G‐quadruplex DNA folds and improving the targeting of G‐quadruplexes by potential anticancer compounds. To better interpret such experiments, classical and replica‐exchange molecular dynamics simulations and fluorescence‐lifetime measurements are used to understand the behavior of a range of Cy3‐based dyes attached to the 3′ end of G‐quadruplex DNA. The simulations revealed that the dyes interact extensively with the G‐quadruplex. Identification of preferred dye positions relative to the G‐quadruplex in the simulations allows the impact of dye–DNA interactions on FRET results to be determined. All the dyes show significant deviations from the common approximation of being freely rotating and not interacting with the host, but one of the Cy3 dye analogues is slightly closer to this case.